The Effect Of Profitability of Company Size Audit Opinion and Audit Delay on Switching Auditors - Meilda Putriandi (Syntax Idea)
This study aims to analyze the effect of profitability, company size, audit opinion, and audit delay on auditor switching. This study consists of four independent variables, namely profitability, company size, audit opinion, and audit delay, and one dependent variable, namely auditor switching. The sample in this study is the basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2018 to 2020. The sampling technique uses purposive sampling because not all populations can be sampled and samples can be taken based on certain criteria. In this study, there were 14 companies that met the criteria of a total observation of 77 companies, so that a sample of 42 financial statement data was obtained. The data analysis technique used is logistic regression analysis with SPSS version 25. The results of this study show that profitability partially has no effect on auditor switching, company size partially does not affect auditor switching, audit opinion partially affects auditor switching, and audit delay partially has no effect on auditor switching.